2019
DOI: 10.1051/0004-6361/201935217
|View full text |Cite
|
Sign up to set email alerts
|

Formation of interstellar propanal and 1-propanol ice: a pathway involving solid-state CO hydrogenation

Abstract: Context. 1-propanol (CH 3 CH 2 CH 2 OH) is a three carbon-bearing representative of the primary linear alcohols that may have its origin in the cold dark cores in interstellar space. To test this, we investigated in the laboratory whether 1-propanol ice can be formed along pathways possibly relevant to the prestellar core phase. Aims. We aim to show in a two-step approach that 1-propanol can be formed through reaction steps that are expected to take place during the heavy CO freeze-out stage by adding C 2 H 2 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 75 publications
1
30
0
Order By: Relevance
“…Previous detections of chemically related species, namely acetaldehyde (CH 3 CHO), acetone (CH 3 COCH 3 ), ethyl methyl ether (C 2 H 5 OCH 3 ), C 2 H 5 CHO and CH 3 CCH, reported from the same dataset by Lykke et al (2017) and Calcutt et al (2019), are also indicated in the table and have been used for a comparison with the chemical model. Qasim et al (2019) already reported a column density upper limit for Ga-n-C 3 H 7 OH of < 1.2 × 10 15 cm −2 at 300 K and < 7.4×10 14 cm −2 at 125 K, using the Band 6 dataset of Taquet et al (2018). Given their same dataset and the correction factor to include the contribution of the other conformers, this estimate is consistent with the results presented here.…”
Section: Column Densitiessupporting
confidence: 90%
See 3 more Smart Citations
“…Previous detections of chemically related species, namely acetaldehyde (CH 3 CHO), acetone (CH 3 COCH 3 ), ethyl methyl ether (C 2 H 5 OCH 3 ), C 2 H 5 CHO and CH 3 CCH, reported from the same dataset by Lykke et al (2017) and Calcutt et al (2019), are also indicated in the table and have been used for a comparison with the chemical model. Qasim et al (2019) already reported a column density upper limit for Ga-n-C 3 H 7 OH of < 1.2 × 10 15 cm −2 at 300 K and < 7.4×10 14 cm −2 at 125 K, using the Band 6 dataset of Taquet et al (2018). Given their same dataset and the correction factor to include the contribution of the other conformers, this estimate is consistent with the results presented here.…”
Section: Column Densitiessupporting
confidence: 90%
“…The final abundances show a decrease compared to the simulation where the molecules are produced through ice-surface reactions, among others. The updated activation energies, taken from the study of Qasim et al (2019) and tested in the simulation E1, do not change the final abundances of the C 3 -species significantly.…”
Section: -Speciesmentioning
confidence: 98%
See 2 more Smart Citations
“…The formation of sugars and their derivates under interstellar conditions was reported by Fedoseev et al (2017) and Nuevo et al (2018). Very recently, propanal and prebiotically relevant 1-propanol could be synthesized at a temperature of 10 K by Qasim et al (2019). The formation of peptide-like molecules, which are possible precursors of amino acids, were synthesized in CH 4 :HNCO ice mixtures upon UV processing (Ligterink et al 2018).…”
Section: Processing Of Grains and Reactions On Grain Surfacesmentioning
confidence: 99%